HUBUNGAN CARA BELAJAR DAN FASILITAS BELAJAR DIRUMAHDENGAN HASIL BELAJAR MATA DIKLAT SISTEM REMSISWA KELAS XI TEKNIK KENDARAAN RINGANSMK NEGERI 2 KEBUMEN JAWA TENGAH - Yulianto Eka Nurcahyo; Pairun Roniwijaya (Jurnal Taman Vokasi, 2013)
The purpose of the study (1) to determine whether there is a positive relationship between learning with the resultslearning outcomes Mechanical brake system students of class XI Light Vehicle Engineering Vocational School of State 2  Kebumen Central Java, (2) to determine whether there is a positive relationship between learning facilities at home with the results learning outcomes Mechanical brake system students of class XI Light Vehicle Engineering Vocational School of State 2 Kebumen Central Java, (3) to determine whether there is a positive relationship between learning styles and learning facilities at home with the results outcomes Mechanical brake system students of class XI Light Vehicle Engineering Vocational School of State 2  Kebumen Central Java.This research was conducted at Vocational School of State 2  Kebumen Central Java school year 2013/2014 on November 14th till 27 December 2013. The population in this study were all students of class XI TKR totaling 64 students and this study used a sampling saturated or study populations so that the entire population were sampled. This research is correlational and ex post facto categorized. Questionnaire data collection techniques and documentation of learning outcomes . The validity of the items were obtained from the product moment correlation. About the reliability of the formula obtained by alpha and declared reliable. Before the data were analyzed first tested the prerequisite analysis is normality test, multicollinearity, and linearity test. Analysis using partial correlation analysis and multiple regression analysis.From the analysis of the results obtained the following results: (1) There is a positive and significant relationship between learning (X1) with learning outcomes Mechanical brake system (Y), (2) There is a positive and significant relationship between learning facilities at home (X2) and learning outcomes Mechanical brake system (Y), (3) There is a positive and significant relationship between learning (X1) and learning facilities at home (X2) together with  learning outcomes Mechanical brake system (Y).